Alu Katentong performance, history, form, and function at a wedding event in Padang Laweh - Syeilendra, Syeilendra; Mayang Sari, Ayuthia (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
Alu Katentong is a traditional Minangkabau art that persists in Nagari Padang Laweh, Tanah Datar Regency. The purpose of this research is to establish that Alu Katentong is an essential and meaningful element in a wedding ceremony. This qualitative study employs a descriptive analysis approach. Data collection techniques include literature review, observation, interviews, documentation, and triangulation. Data analysis involves data clarification, reduction, presentation, and drawing conclusions. The research findings demonstrate that the inclusion of Alu Katentong in wedding ceremonies is a prerequisite for adhering to local customs and traditions, as well as for the preservation of local culture. The performance elements encompass the following: The function of Alu Katentong art serves as a traditional complement to the wedding ceremony procession, provides entertainment and spectacle, functions as a means of communication, acts as a unifying force in society, contributes to cultural preservation, and serves as a medium for educating the community. The presentation takes the form of a coordinated ensemble arrangement comprising several alu, lasuang, and flat stones in a circular formation facing forward (lasuang). This artistic performance commences at noon following various wedding processions leading up to the manjapuik and maanta marapulai procession.